Building electrical systems and distribution networks : an introduction - Belu, Radian (Boca Raton CRC Press, 2020)
"This book covers all important, new and conventional aspects of building electrical systems, power distribution, lighting, transformers and rotating electric machines, wiring and building installations. Solved examples, end of chapter questions and problems, case studies, and design considerations are included in each chapter, highlighting concepts, diverse and critical features of building and industrial electrical systems such as electric or thermal load calculations, wiring, wiring devices, conduits, and raceways, lighting analysis, calculation, selection and design, lighting equipment, luminaires, power quality, building monitoring, noise control, building energy envelope, air conditioning, ventilation, and safety. Two book chapters are dedicated to distributed energy generation, building integrated renewable energy systems, microgrids, DC nanogrids, power electronics, energy management, and energy audit methods which are not often included in building energy textbooks. Support materials are included for interested instructors. Readers are encouraged to write their own solutions while solving the problems, and then refer to the solved examples for more complete understanding of the solutions, concepts and theory"--
Keywords: Electric power distribution; Electric power production